Upgrading of waste oils into transportation fuels using hydrotreating technologies - Sudipta De; Rafael Luque (Biofuel Research Journal, 2014)
The generation of organic waste continues to increase, causing severe environmental pollution. Waste valorization is currently an emerging technology that can address this problem with an extra benefit of producing a range of valued products. In this contribution, we report the current developments in hydrotreating technologies for upgrading waste oil fractions into usable transportation fuels. Particular focus is given on the catalysts selection for a general hydroprocessing technique as well as the competitive role of those catalysts in hydrotreating and hydrocracking processes.